Efektivitas Paket Pereda Terhadap Intensitas Nyeri Dismenore pada Remaja di SMP Negeri 1 Simpur Kabupaten Hulu Sungai Selatan Tahun 2015 - Ni Wayan Kurnia W W; Eviawati Wandira; Nova Kasmita; STIKES Husada Borneo; Alumni STIKES Husada Borneo (Jurnal Kesehatan Indonesia, 2015)
The prevalence of dysmenorrhea in Indonesia amounted to 64.25% from 54.89% occurring primary dysmenorrhea and secondary dysmenorrhea 9.36%. dysmenorrhea can have an impact for the activity or activities of the women, especially teenagers. This study aims to determine the difference between the results of the treatment package quasy reliever this study using an experimental design with pretest-posttest design. The sampling technique used was purposive sampling 53 respondents. Dysmenorrhea pain intensity before the packages are mostly pain relievers were as many as 45 respondents (84.9%), dysmenorrhea pain intensity after the package is done mostly mild pain reliever as many as 46 respondents (86.8%). Based on statistical tests using Wilcoxon results obtained significance (2-tailed) the amount of 0,000 compared with a = 0.05, 0.000 <0,05 so that H0 is rejected and Ha accepted, meaning that there were significant differences in pain intensity dysmenorrhea on young girls between before and after relief package. It concluded that effective relief package to the intensity of dysmenorrhea pain in adolescents in SMP Negeri 1 Simpur Kabupaten Hulu Sungai Selatan Year 2015. It is expected that health professionals to provide care that is safe for teenagers daughter in overcoming painful menstruation preferred non-pharmacological treatment before use drugs.